2019
DOI: 10.1186/s12889-019-7393-x
|View full text |Cite
|
Sign up to set email alerts
|

Activate Your Health, a 3-year, multi-site, workplace healthy lifestyle promotion program: study design

Abstract: Background Workplace Health Promotion Programs (WHPP) have been shown to be an efficient way of improving workers’ health. These programs can be incorporated in the worker’s daily schedule and improve their productivity at work. Improving employees’ health also benefits the employers by increasing their return on investment and lowering healthcare costs. The Activate Your Health program, created by Capsana in 2015, is a WHPP targeting multiple lifestyle habits for a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…De ese modo, se encontraron cinco artículos que describen el alto riesgo que tienen los trabajadores de presentar obesidad en las empresas; así lo mencionan las investigaciones orientadas en la promoción de la salud, los autores Contreras et al (11) (16); teniendo en cuenta los resultados de trabajadores con obesidad y los riesgos a lo que se exponen, es necesario promover una cultura de promoción de la salud en el lugar de trabajo, con el fin de favorecer un ELS. De tal forma, se reconoce el alto riesgo que representa el sobrepeso y la obesidad en la incidencia de varias enfermedades crónicas como: hipertensión arterial y enfermedad isquémica coronaria.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De ese modo, se encontraron cinco artículos que describen el alto riesgo que tienen los trabajadores de presentar obesidad en las empresas; así lo mencionan las investigaciones orientadas en la promoción de la salud, los autores Contreras et al (11) (16); teniendo en cuenta los resultados de trabajadores con obesidad y los riesgos a lo que se exponen, es necesario promover una cultura de promoción de la salud en el lugar de trabajo, con el fin de favorecer un ELS. De tal forma, se reconoce el alto riesgo que representa el sobrepeso y la obesidad en la incidencia de varias enfermedades crónicas como: hipertensión arterial y enfermedad isquémica coronaria.…”
Section: Discussionunclassified
“…En cuatro artículos se observó que utilizaron un instrumento validado, como la herramienta de evaluación del entorno laboral saludable (HWEAT, por su sigla en inglés). Que es un recurso para que las unidades y organizaciones de atención al usuario, evalúen el entorno laboral y rastreen el progreso en su camino hacia la excelencia de las organizaciones (16). Según la revisión elaborada hasta la fecha, se desconoce otro instrumento que presente alta validez y confiabilidad en dicho objetivo.…”
Section: Discussionunclassified
“…Activate Your Health is a WHPP created by Capsana 27 . It includes a research component and is evaluated in eight companies in Quebec, Canada with the partnership of the Public Health Agency of Canada 28 . Participating companies are located in a variety of sectors ranging from bank-related organizations to graveyard administration.…”
Section: Methodsmentioning
confidence: 99%
“…27 It includes a research component and is evaluated in eight companies in Quebec, Canada with the partnership of the Public Health Agency of Canada. 28 Participating companies are located in a variety of sectors ranging from bank-related organizations to graveyard administration. Participating companies picked the following options of this WHPP: Control, Light, Moderate, and High.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…For example, a study protocol for a life-course, multiple HRLB intervention 'MoBILE' was identified (Bendtsen et al, 2020). Alongside an ongoing three-year workplace health promotion programme study 'activate your health' (Kugathasan et al, 2019) which included staff from 11 private sector organisations and offered several interventions to explore the impact of different combinations of lifestyle interventions on behaviour change and health improvement. Such interventions aim to address the effects of clustered lifestyle behaviours and their higher associated risk for chronic disease (Myint et al, 2009).…”
Section: Summary Of Findingsmentioning
confidence: 99%